Multi Drug-Resistant Tuberculosis in Semarang City - Cahyani, Tika Dwi; Rahayu, Sri Ratna; Jazilatun, Fina; Mesrzistya, Aufina Nur Ayu (Public Health Perspective Journal, 2021)
The number of cases of Multi-Drug Resistant Tuberculosis (MDR-TB) in Semarang City increased from year to year. Case data from 2016-2019 in 22 cases, 35 cases, 68 cases, and 63 cases. The purpose of this research is to describe the incidence of MDR-TB in Semarang City. The research was conducted from August - October 2020 with a simple type of descriptive analysis quantitative research. The number of samples is 52 with purposive sampling techniques. The instruments used are questionnaires and medical records. Data is analyzed with descriptive analysis. The results showed that the majority of MDR-TB patients in the Semarang City area are productive (76.9%), male gender (61.5%), an elementary education level (46.2%), not working (47.1%), low income (46.2%), low income (46.2%), 90.4%), severe Anti-Tuberculosis Drugs side effects (76.9%), no previous treatment history (46.2%), contact with people with TB/MDR-TB (53.8%), low drug compliance (59.6%), smokers passive (53.8%), no comorbidity (53.8%), high motivation (84.6%), malnutrition status (71.2%), low health costs (67.3%), good health facilities (67.3%), good health officer attitude (83.7%), access to close health services (73.1%), high family support (63.5%), and active role of watchdog swallows drugs good (51.9%).